Non-enzymatic glucose sensing by enhanced Raman spectroscopy on flexible 'as-grown' CVD graphene1. Issue 12 (21st June 2015) - Chattopadhyay, Surojit; Li, Mau-Shiun; Kumar Roy, Pradip; Wu, C. T.
<x xml:space="preserve">Abstract</x> Unmodified, as-grown few layer graphene (on copper) have been used for glucose sensing using Raman spectroscopy. The origin of the graphene enhanced Raman spectroscopy (GERS) signal of glucose is attributed to a charge transfer from glucose to graphene.